BETWEEN CLIENTELISM AND PATRIMONIALISM: LOCAL POLITICS OF THE PHILIPPINES AND INDONESIA - Ujang Komarudin; Pitut Pramuji (JWP (Jurnal Wacana Politik), 2023)
Erik Kuhonta, a Southeast Asian expert, describe in his article on institution of the states in Southeast Asia that among the spectrum of clientelism and regal-rational bureaucracy, only Singapore and Malaysia could be considered as having an administrative system of rule and law based – of administrative state – the closest to being labeled as legal-rational bureaucracy. Among others he observed, the Philippines is categorized as a patrimonial system, whilst Thailand and Indonesia are recognized as in the middle, with some patrimonial practices still occurring but functioning bureaucracy legal system. This study tries to find the answer to these questions: How do the clientelism and patrimonialism practices in democratized Indonesia and the Philippines local politics? The study concludes that both in Indonesia and the Philippines patronage politics is very much marring the democratization process, economic development, welfare parity, and bureaucratic reform through practices of various kinds of clientelistics approach. Democratization is not a strategy for the elimination of clientelism and patrimonialism, moreover we see meritocratic and Weberian legal-rational bureaucracy still existing in countries with clientelism and patronage politics, such as Taiwan, Japan, and South Korea, or in countries that do not need full-fledge democracy, such as Singapore and Malaysia. We could even see clientelism being regulated in more developed democracy. This study shows that in countries that has clientelism practices yet do not have the effect of corruption and could manage poverty reduction program has society of better economic welfare and higher education background.